Glycemic control after sleeve gastrectomy in Taif Hospitals, Kingdom of Saudi Arabia. Issue 1 (31st December 2022) - Abduljabbar, Maram H.; Nafea, Ola E.; Alahmari, Wafa M.; Alharthi, Amjad A.; Alorabi, Alanoud S.; Alharthi, Shahad J.; Alosami, Norah A.; Larbi, Noureddine; Alshareef, Khaled
Abstract : This study was designed to assess the glycemic control after sleeve gastrectomy surgeries in overweight and obese patients with T2DM as well as the associated factors that may affect glycemic control in those patients. We conducted a retrospective study based on retrieving the required information from patient's files in Medical Records Departments for type II diabetic overweight and obese patients who underwent laparoscopic sleeve gastrectomy (LSG), in Taif, from January 2017 to December 2019. The follow-up duration for all patient was three-to-six months postoperatively. We found that LSG achieved a significant glycemic control in overweight and obese patients with T2DM. Preoperatively, mean ± SD fasting blood glucose, random blood glucose and hemoglobin A1C were 160.7 ± 65.6 mg/dL, 237.4 ± 66.9 mg/dL and 8.4 ± 1.5%, respectively. Postoperatively, mean ± SD fasting blood glucose, random blood glucose and hemoglobin A1C were 103.4 ± 36 mg/dL, 113.6 ± 15.7 mg/dL and 6.2 ± 0.9% ( P < .001, for each). Multivariable logistic regression analysis revealed that increasing age was the most significant independent predictor that affect diabetic control in our study [odds ratio, 1.141, 95% confidence interval (1.015 to 1.282), P = .027)]. We concluded that LSG is a successful treatment option for glycemic control in overweight and obese patients with T2DM especially younger patients usually three-to-six months following surgery.